Analisis Hukum Bentuk-Bentuk Radikalisme pada Pendidikan Anak Usia Dini - Ida Hanifah; Nurhilmiyah Nurhilmiyah (Mahesa Research Center, 2022)
Indeed, at an early age, religious values should be instilled in accordance with the beliefs held by their parents. So that children in the future have better morals, accompanied by religious knowledge that is taught from an early age. It should be supported to continuously animate religious knowledge. So that children's lives in the future remain in the goodness that is recommended by the teachings of revelation. In fact, what is currently happening is that teaching religious knowledge from an early age is called by the government as a radical teaching, so the question arises whether teaching and practicing religious activities is included in a radical understanding? When it is said to be radical, it means that all religious people are adherents of radicalism. It is important to examine the existence of forms of radicalism in early childhood education institutions. This study uses empirical legal research methods by taking research locations in two kindergartens. The conclusion of this study is based on the results of our team's analysis, that there are no forms of radicalism from teaching materials, ways of delivering and other matters related to the implementation of early childhood education, which have anything to do with radicalism. Suggestions to the government, to look more fairly and wisely, so that there is no longer the assumption that radicalism is found in early childhood education.